catena-Poly[[[tetra-kis(μ-2-butenoato)dicopper(II)] -μ- 2-butenoato-[diaqua-(2-butenoato)holmium(III)]-di - 2-butenoato-[diaqua-(-μ- 2-butenoato)holmium(III)]-μ-2-butenoato] trihydrate] - Perec, Mireille (2008)
The title compound {[Cu2Ho2(C4H5O2)10(H2O)4]·3H2O}n, is a one-dimensional 3d/4f organic-inorganic hybrid complex, the HoIII member of the isotypic lanthanoid series with Ln = GdIII, ErIII and YIII. The structure shows an alternation of Cu2 and Ho2 dinuclear units bridged by the ligands and hydrogen bonds only. The chains are composed of Cu2 classical dinuclear [eta]1:[eta]1:[mu]2 fourfold bridges [Cu...Cu = 2.6417 (9) Å] and of Ho2 units bridged by two [eta]2:[eta]1:[mu]2 carboxylate units. This results in distorted square-based pyramidal CuO5 units and irregular HoO9 units. The alternating Cu2 and Ho2 units are bridged into linear arrays along the a axis by a set of one [eta]2:[eta]1:[mu]2 carboxylate O atom and two hydrogen bonds with Cu...Ho separations of 4.4883 (10) and 4.5086 (10) Å. The distance between adjacent chains, as calculated by the closest and furthest distances between two chains, covers the range 10-14 Å. The H atoms of the water molecules could not be located, but the O...O separations for these species suggest the presence of O-H...O hydrogen bonds.